Corporate motivation: a study in companies in the tourism sector in the city of Carnaubal – Ceará (Research, Society and Development, 2022)
The objective of the study is to analyze the motivational factors applied to the tourist sector of Carnaubal - Ceará. Methodological procedures: Qualitative study, carried out through the application of semi-structured interviews with employees and employers. Results: It was noticed that, in the view of employers, the motivational factors for the employee generate noticeable impacts for the company, ensuring that the motivated employee influences the development of the organization. Based on the answers given by the employees, it was noticed that they have an average knowledge and understanding of the importance of employee motivation in the work environment. Conclusion: Employees of both companies have a limited view when it comes to organizational motivation, but there is still confusion in correlating their level of motivation with their activities.